2019
DOI: 10.1111/een.12831
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide to DNA metabarcoding for entomological ecologists

Abstract: 1. DNA metabarcoding is a cost-effective species identification approach with great potential to assist entomological ecologists. This review presents a practical guide to help entomological ecologists design their own DNA metabarcoding studies and ensure that sound ecological conclusions can be obtained.2. The review considers approaches to field sampling, laboratory work, and bioinformatic analyses, with the aim of providing the background knowledge needed to make decisions at each step of a DNA metabarcodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 122 publications
(136 reference statements)
0
112
0
Order By: Relevance
“…This natural variation in biomass can jeopardize the detection of small and rare specimens (Deagle et al, 2018), especially when taking PCR effects into account (Kelly, Shelton and Gallego, 2019). To maximise taxa detection in bulk samples showing substantial specimen biomass variation (Aylagas et al, 2016), size sorting might be required (Liu et al, 2019). Marine arthropod bulk samples are commonly size fractionated by sieving (Cowart et al, 2015;Leray and Knowlton, 2015;Wangensteen and Turon, 2017;Wangensteen et al, 2018) before metabarcoding.…”
Section: Introductionmentioning
confidence: 99%
“…This natural variation in biomass can jeopardize the detection of small and rare specimens (Deagle et al, 2018), especially when taking PCR effects into account (Kelly, Shelton and Gallego, 2019). To maximise taxa detection in bulk samples showing substantial specimen biomass variation (Aylagas et al, 2016), size sorting might be required (Liu et al, 2019). Marine arthropod bulk samples are commonly size fractionated by sieving (Cowart et al, 2015;Leray and Knowlton, 2015;Wangensteen and Turon, 2017;Wangensteen et al, 2018) before metabarcoding.…”
Section: Introductionmentioning
confidence: 99%
“…NUMTs have long been recognised to confound barcoding with Sanger and high throughput sequencing (e.g., Song et al 2008; Shokralla et al 2014; Creedy et al 2019), and the potential impact of NUMTs on metabarcoding has been discussed widely (e.g., Ramirez-Gonzalez et al 2013; AndĂșjar et al 2018b; Elbrecht et al 2018; Liu et al 2019; Delsuc & Ranwez 2020). NUMTs are likely to be consequential in metabarcoding because of: (i) the widespread use of degenerate primers for metabarcoding (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, species were assigned for 75% of the fragments analysed in a study of red‐headed wood pigeon diet (Ando et al., 2013), for ≄60% when examining the diet of a bear (De Barba et al., 2014), and dietary analyses of the black wheatear detected the presence of animal DNA in 94 samples out of 112 using 18S, thus yielding 91 taxa from 21 orders of which 10% were assigned to the genus or species level (da Silva et al., 2019). Obtaining longer amplicons provides a well‐known advantage for our long metabarcoding approach because it enhances the precision of taxonomic identification (Heeger et al., 2018; Jamy et al., 2020; Liu et al., 2020; Piper et al., 2019; Porter & Golding, 2011). Furthermore, the approach developed here not only allowed us to amplify both barcodes of short to medium size, in cases of degraded DNA, but also and especially of long size (>500–650 bp and more), which is believed to increase the taxonomic affiliation at the species level.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the approach developed here not only allowed us to amplify both barcodes of short to medium size, in cases of degraded DNA, but also and especially of long size (>500–650 bp and more), which is believed to increase the taxonomic affiliation at the species level. Indeed, shorter DNA fragments (e.g., 100 bp or less) are more likely to be sequenced, while longer DNA fragments provide a better taxonomic identification and resolution (Liu et al., 2020). Analyses made on degraded DNA samples demonstrated that few very informative barcodes such as COI , of shorter size between 135 bp (Hajibabaei et al., 2006) and 250 bp (Meusnier et al., 2008), can reliably identify animal species, if they target an appropriate placement within the larger barcode region (Elbrecht et al., 2019).…”
Section: Discussionmentioning
confidence: 99%